Evaluation of Accreditation and National Examination using Multilevel Generalized Structured Component Analysis - Susetyo, Budi; Fitrianto, Anwar (FKIP Universitas Lampung, 2022)
Evaluation of Accreditation and National Examination using Multilevel Generalized Structured Component Analysis. Hierarchical elements or higher levels often influence school accreditation and the national exam because education units are nested in the characteristics of the province. Objectives: This study aims to evaluate the relationship between accreditation and the national exam at the level of Junior high school/Madrasa in Java which are nested in province. Methods: The analysis employs multilevel GSCA analysis (MGSCA). Findings: UNBK has good convergent validity and it can explain each of the subjects tested in each province up to more than 90%. Concerning the estimates of path coefficients, the study found eight patterns of relationship between SNP and UNBK that have a significant effect in the six provinces. Conclusion: The relationship between content and competency standard for UNBK shows that there are significant differences in all provinces in Java island. This shows that provincial characteristics affect school quality. The model can explain the total variability of all variables is 72.44%. Keywords: multilevel generalized structured component analysis, national education standards, national examination.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202223